Exploring Online Shopping Trends: The Impact of Lifestyle on Gen Z Students' Purchasing Decisions on Shopee - Kinanti, Virginia Eka Putri; Solichah, Afifatus; Handayani, Novi; Maghfiroh, Mellya Imroatul; Abdiana, Eka Yuli; Ramadani, Putri Amalia; Afiqfah, Nur (Journal of Economics, Management and Accounting (JEMA), 2024)
How their lifestyle and influence on Shopee purchasing decisions is the purpose of this study. Gen Z, known as digital natives, exhibit unique shopping behavior patterns driven by technological advances and easy access to information. This study collects data quantitatively through a survey method to collect data from 61 generation Z students from the faculty of economics at the University of Nahdlatul Ulama Sidoarjo class of 2021. The results showed that online shopping trends have a significant effect on purchasing decisions and lifestyle has a significant effect on purchasing decisions. This research provides detailed insights into the online shopping behavior of Gen Z students and helps e-commerce industry stakeholders develop more efficient marketing strategies that meet the needs and preferences of younger customers.